THE EFFECT OF EFFECTIVENESS OF ADVERTISING TAX COLLECTION AND MATERIAL COMPLIANCE WITH REGIONAL REVENUE OF GORONTALO - Ismet Sulila (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The research aimed to find out the Effect of Effectiveness of Advertisement Tax Collection and Material Compliance towards Local Own- Source Revenue (hereinafter referred to as PAD) of Gorontalo. The approach used in this research was a quantitative method. The data source of this research was primary data performed by distributing a questionnaire to respondents who have met the research samples standard. The technique of data analysis used multiple regression analysis by using SPSS program assistance. The findings of the research showed that (1) the effectiveness of advertisement tax collection had a positive and significant effect on the PAD in Gorontalo. (2) The material compliance had a positive and significant effect on the PAD in Gorontalo. The meaning of the positive coefficient showed that the higher material compliance would lead to the more optimal PAD. (3) The effectiveness of advertisement tax collection and material compliance, simultaneously, had a significant effect on the PAD in Gorontalo. The value of determination coefficient was 0,728 or it meant 72,8% of PAD in Gorontalo variability could be explained by the effectiveness of advertisement tax collection and material compliance, whereas the rest 27,2% could be explained by other variables excluded in this research such as factors which encompassed knowledge, integrity, motivation at work, discipline at work, internal control system, organizational commitment, and work ethic.